Resin-based composite material and preparation method thereof

By using conductive glass fibers and glass fibers in resin-based composite materials and installing modified carbon nanomaterials on the surface of conductive glass fibers, the safety and reliability problems of existing composite materials when subjected to lightning strikes or electromagnetic interference are solved, and the safety and reliability of existing composite materials are achieved. The balance between conductivity and mechanical properties is achieved.

CN119391136APending Publication Date: 2025-02-07ZHENSHI GRP HUAZHI RES INST (ZHEJIANG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411711325.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing glass fiber reinforced epoxy resin composites have safety and reliability problems when subjected to lightning strikes or electromagnetic interference, making it difficult to achieve a balance between conductivity and mechanical properties.

Method used

By using conductive glass fibers and glass fibers as reinforced fiber layers in the resin-based composite material and providing modified carbon nanomaterials on the surface of the conductive glass fibers, a conductive coating film is formed to improve the lightning protection performance of the composite material.

Benefits of technology

It achieves the improvement of lightning protection performance of composite materials while maintaining good mechanical properties, and ensures both mechanical strength, lightning protection performance and processing performance of the material by controlling the mass ratio of conductive glass fibers and glass fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391136A_ABST
    Figure CN119391136A_ABST
Patent Text Reader

Abstract

The invention discloses a resin-based composite material and a preparation method thereof, and relates to the technical field of composite materials. The resin-based composite material comprises a resin matrix and a reinforced fiber layer, and the reinforced fiber layer is filled with the resin matrix; the reinforced fiber layer comprises conductive glass fibers and glass fibers in a mass ratio of (0.5-2.0): 1. According to the invention, the conductive glass fibers and the glass fibers are used as the reinforced fiber layer, so that the composite material is endowed with excellent lightning protection performance while the mechanical property of the composite material is improved, and the composite material has good processability by controlling the mass ratio of the conductive glass fibers to the glass fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a resin-based composite material and a preparation method thereof. Background Art

[0002] Resin-based composite materials are a type of material that is made by using resin as a matrix and various reinforcing materials through a composite process. Among them, epoxy resin has good mechanical and thermal stability and is easy to process and shape. It is a key component of lightweight, high specific strength and specific modulus, and designable glass fiber reinforced epoxy resin composite materials. It is widely used in aerospace, wind power and other fields. However, due to the inherent insulation of epoxy resin and glass fiber, once materials such as aircraft and blades made of this composite material are struck by lightning or electromagnetic interference, it will seriously threaten the safety and reliability of the composite material application.

[0003] In order to meet the requirements of lightning protection for glass fiber reinforced epoxy resin composite materials, it is necessary to modify the epoxy resin to improve its electrical conductivity. In the related art, a blending modification method is often used to mix conductive fillers into epoxy resin to obtain glass fiber reinforced epoxy resin composite materials with excellent electrical conductivity. However, it is difficult to achieve a balance between electrical conductivity and mechanical properties by adding a large amount of conductive fillers to improve the electrical conductivity of epoxy resin. Generally, it is at the expense of the mechanical properties of the epoxy resin matrix, which reduces the practicality of the composite material. Summary of the invention

[0004] In order to solve the above technical problems, the present application aims to provide a resin-based composite material and a preparation method thereof, wherein the resin-based composite material has good mechanical properties and excellent lightning protection performance.

[0005] According to a first aspect of the present application, there is provided a resin-based composite material, the resin-based composite material comprising a resin matrix and a reinforcing fiber layer, the resin matrix being filled into a layer of the reinforcing fiber layer;

[0006] The reinforcing fiber layer includes conductive glass fiber and glass fiber in a mass ratio of 0.5-2.0:1.

[0007] In some embodiments of the present application, the mass percentage of each component of the resin-based composite material to the total mass of the resin-based composite material is as follows:

[0008] Resin matrix 30-50wt%;

[0009] Reinforced fiber layer 50-70wt%.

[0010] In some embodiments of the present application, the conductive glass fiber includes a glass fiber matrix and a surface treatment layer disposed on the surface of the glass fiber matrix.

[0011] In some embodiments of the present application, the surface treatment layer includes a surface treatment agent, and the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:

[0012]

[0013] Wherein, the conductive agent includes modified carbon nanomaterials.

[0014] In some embodiments of the present application, the modified carbon nanomaterial includes a carbon nanomaterial and a modifier, the modifier includes an amine modifier, and the carbon chain length of the amine modifier is greater than or equal to C10.

[0015] In some embodiments of the present application, the mass ratio of the carbon nanomaterial to the modifier is 1:0.5-2.0.

[0016] In some embodiments of the present application, the modifier includes a combination of one or more of dodecyldimethylbenzylammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium;

[0017] The film-forming agent includes one of water-based epoxy resin emulsion and water-based polyurethane emulsion or a combination of the two;

[0018] The coupling agent includes one of epoxy silane coupling agents and amino silane coupling agents or a combination of the two.

[0019] In some embodiments of the present application, the surface treatment agent further comprises:

[0020] A penetrant, the mass of which accounts for 0.5-2wt% of the total mass of the surface treatment agent;

[0021] and / or, a lubricant, wherein the mass of the lubricant accounts for 0.5-2wt% of the total mass of the surface treatment agent.

[0022] According to a second aspect of the present application, a method for preparing a resin-based composite material is provided. The method for preparing a resin-based composite material is used to prepare the resin-based composite material as described above. The method comprises:

[0023] Arranging the conductive glass fiber and the glass fiber to obtain warp yarn and weft yarn;

[0024] Weaving the warp yarns and the weft yarns under a preset tension to form the reinforcing fiber layer;

[0025] The resin matrix is ​​impregnated into the reinforcing fiber layer to obtain the resin-based composite material.

[0026] In some embodiments of the present application, the preset tension is 50-150 cN.

[0027] The technical solution provided by this application may have the following beneficial effects:

[0028] The present application uses conductive glass fiber and glass fiber as reinforcing fiber layers, which can improve the mechanical properties of the composite material while giving it excellent lightning protection performance. In addition, by controlling the mass ratio of conductive glass fiber and glass fiber, the composite material can have both good mechanical properties and processability.

[0029] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0031] Figure 1 It is a schematic diagram of the structure of a resin-based composite material layer according to an exemplary embodiment.

[0032] Figure 2 is a schematic diagram of a cross-sectional structure of a conductive glass fiber according to an exemplary embodiment.

[0033] Figure 3 FIG. 4 is a surface morphology diagram of a conductive glass fiber according to an exemplary embodiment.

[0034] Figure 4 is a flow chart of a method for preparing a surface treatment agent according to an exemplary embodiment.

[0035] Figure 5 is a flow chart of a method for preparing a conductive agent according to an exemplary embodiment.

[0036] Figure 6 The present invention is a flow chart of a method for preparing conductive glass fiber according to an exemplary embodiment.

[0037] Figure 7 The present invention is a flow chart of a method for preparing a resin-based composite material according to an exemplary embodiment.

[0038] Figure 8 is a diagram showing a structure of a reinforced fiber layer according to an exemplary embodiment.

[0039] Figure 9a This is a photograph of the conductive agent in Preparation Example 1 after being left standing for 0 hours.

[0040] Figure 9bThis is a photograph of the conductive agent in Preparation Example 1 after being left to stand for 24 hours.

[0041] Reference numerals:

[0042] 1. Glass fiber matrix; 2. Surface treatment layer;

[0043] 10. Reinforcement fiber layer; 20. Resin matrix. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in combination with the embodiments of the present application and the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.

[0045] The present application provides a resin-based composite material, which includes a resin matrix and a reinforcing fiber layer, wherein the resin matrix is ​​filled into the layer of the reinforcing fiber layer; the reinforcing fiber layer includes conductive glass fiber and glass fiber in a mass ratio of 0.5-2.0:1. Conductive glass fiber and glass fiber are used as the reinforcing fiber layer, which can improve the mechanical properties of the composite material while giving it excellent lightning protection performance. In addition, by controlling the mass ratio of conductive glass fiber and glass fiber, the composite material can have good processing performance.

[0046] Some specific implementation modes described below are intended to facilitate those skilled in the art to understand the present embodiment, and the present embodiment is not limited to some specific implementation modes described below.

[0047] like Figure 1 As shown, an exemplary embodiment of the present application provides a resin-based composite material, which includes a resin matrix 20 and a reinforcing fiber layer 10, wherein the resin matrix 20 is filled into the layer of the reinforcing fiber layer 10; the reinforcing fiber layer 10 includes conductive glass fibers and glass fibers in a mass ratio of 0.5-2.0:1.

[0048] In this embodiment, conductive glass fiber and glass fiber are used as the reinforcing fiber layer 10, which can improve the mechanical properties of the composite material and give it excellent lightning protection performance. The conductive glass fiber refers to a glass fiber material with conductive properties, for example, a common glass fiber matrix 1 without conductive properties is surface-treated to form a conductive coating; the glass fiber refers to a common glass fiber material without conductive properties, which can be the same as the glass fiber matrix 1 in the conductive glass fiber that has not been surface-treated.

[0049] The mass ratio of the conductive glass fiber to the glass fiber needs to be controlled within a suitable range. If the amount of the conductive glass fiber is too low, the lightning protection performance of the composite material will be affected; and if the amount of the conductive glass fiber is too high, the wetting effect of the resin matrix 20 on the reinforced fiber layer 10 will be affected, resulting in a long wetting time, which will affect the production efficiency and processing characteristics of the product; therefore, in this embodiment, the mass ratio of the conductive glass fiber to the glass fiber is controlled at 0.5-2.0:1, so that the composite material has both mechanical strength, lightning protection and processing performance. Exemplarily, the mass ratio of the conductive glass fiber to the glass fiber can be 0.5:1, 0.8:1, 1:1, 1.5:1, 2.0:1. The mass ratio of the conductive glass fiber to the glass fiber can also be any ratio between the exemplary ratios, for example, the mass ratio of the conductive glass fiber to the glass fiber can also be any ratio between 0.8-1.5:1.

[0050] It should be noted that Figure 1 It is only for the convenience of illustration to show the interlayer relationship between the resin matrix 20 and the reinforcing fiber layer 10. However, in actual products, the boundary between the resin matrix 20 and the reinforcing fiber layer 10 is not necessarily clear, and part of the resin matrix 20 will be filled into the layer of the reinforcing fiber layer 10 to fill the gaps in the reinforcing fiber layer 10, and the other part of the resin matrix 20 will be coated on the surface of the reinforcing fiber layer 10.

[0051] In an exemplary embodiment, the mass percentage of each component of the resin-based composite material to the total mass of the resin-based composite material is as follows:

[0052] Resin matrix 20 30-50wt%;

[0053] Reinforced fiber layer 10 50-70wt%.

[0054] In this embodiment, the resin matrix 20 can maintain good comprehensive properties such as mechanical strength and impact resistance by controlling the amount of the resin matrix 20 and the reinforcing fiber layer 10. The resin matrix 20 can be, for example, an epoxy resin system, for example, the resin matrix 20 includes the following raw materials in percentage by weight: 76 wt% epoxy resin; 24 wt% curing agent.

[0055] For example, in one embodiment, the percentage of the mass of each component of the resin-based composite material to the total mass of the resin-based composite material is as follows:

[0056] Resin matrix 30wt%;

[0057] Reinforced fiber layer 70wt%.

[0058] In one embodiment, the percentage of the mass of each component of the resin-based composite material to the total mass of the resin-based composite material is as follows:

[0059] Resin matrix 35wt%;

[0060] Reinforced fiber layer 65wt%.

[0061] In another embodiment, the percentage of the mass of each component of the resin-based composite material to the total mass of the resin-based composite material is as follows:

[0062] Resin matrix 45.5wt%;

[0063] Reinforced fiber layer 54.5wt%.

[0064] In another embodiment, the percentage of the mass of each component of the resin-based composite material to the total mass of the resin-based composite material is as follows:

[0065] Resin matrix 50wt%;

[0066] Reinforced fiber layer 50wt%.

[0067] In an exemplary embodiment, if Figure 2 As shown, the conductive glass fiber includes a glass fiber-based composite material and a surface treatment layer 2 arranged on the surface of a glass fiber matrix 1 .

[0068] In this embodiment, a surface treatment layer 2 is provided on the surface of the glass fiber matrix 1 to obtain a conductive glass fiber having conductive properties, thereby improving the lightning protection of the composite material.

[0069] The surface morphology of the conductive glass fiber in this embodiment is as follows Figure 3 As shown, according to Figure 3 It can be seen that the surface of the glass fiber is an obviously rough surface, which indicates that the surface of the conductive glass fiber in this embodiment has a surface treatment layer 2 .

[0070] In an exemplary embodiment, the surface treatment layer 2 includes a surface treatment agent, and the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:

[0071]

[0072] Wherein, the conductive agent includes modified carbon nanomaterials.

[0073] The surface treatment agent in this application is an emulsion-like substance, which is formed by dispersing a conductive agent, a film-forming agent, a coupling agent, etc. in water. In order to make the surface treatment agent have better comprehensive performance, in addition to controlling the content of each component in the surface treatment agent, it is also necessary to make each component able to maintain stability in water for a long time to avoid changes in the actual component content of the product due to precipitation or stratification of the components during use. Among them, due to the large specific surface area and low polarity of carbon nanomaterials, they are prone to agglomeration and stratification in water, affecting their dispersibility and stability in water.

[0074] Based on this, in an exemplary embodiment, the modified carbon nanomaterial includes a carbon nanomaterial and a modifier, the modifier includes an amine modifier, and the carbon chain length of the amine modifier is greater than or equal to C10.

[0075] In this embodiment, the modifier is a long carbon chain amine modifier with a carbon chain length greater than or equal to C10. When the carbon nanomaterial is treated with the modifier, on the one hand, the long carbon chain can be adsorbed on the surface of the carbon nanomaterial by non-covalent modification to improve the adhesion. The conductive agent thus formed can be stably dispersed in water. In the surface treatment agent of the aqueous system, it can remain stationary for more than 24 hours without stratification, thereby improving the stability of the surface treatment agent and its uniform distribution on the glass fiber surface. However, if a modifier without a long carbon chain or a short carbon chain is used, it is difficult to maintain the long-term dispersion stability of the carbon nanomaterial in water, and it is easy to form agglomerates on the surface of the glass fiber, affecting the conductivity and mechanical properties of the composite material. On the other hand, when the film-forming agent and the coupling agent are materials containing epoxy groups (such as epoxy resin), under the action of a pH adjuster, the amine group in the amine modifier reacts with the epoxy group in the film-forming agent and the coupling agent. The conductive coating film formed can improve the wear resistance of the conductive glass fiber and the adhesion of the carbon nanomaterial, thereby allowing the glass fiber to maintain conductivity for a longer period of time.

[0076] In an exemplary embodiment, the mass ratio of the carbon nanomaterial to the modifier is 1:0.5-2.0.

[0077] If the amount of modifier is too low, the dispersibility of carbon nanomaterials in water will decrease, affecting the uniformity of its distribution on the surface of glass fiber, easily causing interface defects, and affecting the current continuity on the surface of glass fiber, which is not conducive to the decrease of surface resistance of glass fiber; if the amount of modifier is too high, it will affect the chemical reaction between the surface treatment agent and the glass fiber, resulting in a decrease in the interface bonding force between the conductive coating and the glass fiber, and a decrease in wear resistance. Therefore, in this embodiment, by controlling the mass ratio of carbon nanomaterial to modifier to 1:0.5-2.0, the carbon nanomaterial can have good dispersibility in water, and the conductive coating can maintain a good interface bonding force with the glass fiber. Exemplarily, the mass ratio of carbon nanomaterial to modifier is 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2.0.

[0078] In an exemplary embodiment, the modifier includes a combination of one or more of dodecyldimethylbenzyl ammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium.

[0079] In this embodiment, the long-chain amine modifier can be dodecyldimethylbenzyl ammonium chloride and / or octadecyl-(2-sulfite)-ethyldimethylammonium. The above-mentioned modifiers can not only make the carbon nanomaterials maintain good dispersibility in water, but also make the conductive coating on the surface of the glass fiber have good wear resistance, thereby allowing the glass fiber to maintain long-term conductivity.

[0080] In an exemplary embodiment, the film former includes one or a combination of waterborne epoxy resin emulsion and waterborne polyurethane emulsion.

[0081] In this embodiment, the aqueous epoxy resin emulsion and the aqueous polyurethane emulsion have good dispersibility in water, so that each component of the surface treatment agent has good dispersion stability. The film-forming agent can be selected from one of the aqueous epoxy resin emulsion and the aqueous polyurethane emulsion, or the aqueous epoxy resin emulsion and the aqueous polyurethane emulsion can be compounded according to a mass ratio of 2:1. Among them, the aqueous epoxy resin emulsion can be a model such as 5522-1, EP-51, etc. The aqueous polyurethane emulsion can be PU-601 or 8081.

[0082] In an exemplary embodiment, the coupling agent includes one or a combination of an epoxy silane coupling agent and an amino silane coupling agent.

[0083] Silane coupling agent is an organosilicon compound that can improve the bonding force between the conductive coating formed by the surface treatment agent and the glass fiber. In this embodiment, the coupling agent can be one of an epoxy silane coupling agent and an amino silane coupling agent, or the epoxy silane coupling agent and the amino silane coupling agent can be compounded in a mass ratio of 2:1. Among them, the epoxy silane coupling agent can be, for example, a composition of one or more of 3-glycidyloxypropyl triethoxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, and 3-glycidyloxypropyl methyl diethoxysilane. The amino silane coupling agent can be, for example, a composition of one or two of γ-aminopropyl triethoxysilane and γ-aminopropyl trimethoxysilane.

[0084] In an exemplary embodiment, the surface treatment agent further comprises:

[0085] Penetrant, the mass of the penetrant accounts for 0.5-2wt% of the total mass of the surface treatment agent;

[0086] and / or, a lubricant, the mass of the lubricant accounting for 0.5-2wt% of the total mass of the surface treatment agent.

[0087] In this embodiment, by adding a penetrant to the surface treatment agent, the surface energy of the surface treatment agent can be reduced, the wettability and adhesion of the surface treatment agent to the glass fiber can be improved, and the surface polarity and reactivity of the conductive glass fiber can also be enhanced. For example, the mass of the penetrant accounts for 0.5wt%, 1wt% or 2wt% of the total mass of the surface treatment agent. The penetrant can be, for example, a JFC type fatty alcohol polyoxyethylene ether.

[0088] By adding a lubricant to the surface treatment agent, the continuity and uniformity of the conductive coating formed on the surface of the glass fiber can be improved, and the bundling and processing performance of the glass fiber can be improved. Exemplarily, the mass of the lubricant accounts for 0.5wt%, 1wt% or 2wt% of the total mass of the surface treatment agent. The lubricant can be polyethylene glycol, and the polyethylene glycol can be, for example, PEG-400, PEG-800, PEG-1000, etc.

[0089] In an exemplary embodiment, if Figure 4 As shown, the present application provides a method for preparing a surface treatment agent, comprising:

[0090] S110, mixing a conductive agent, a film-forming agent, a coupling agent and water to obtain a premix.

[0091] In step S110, the conductive agent, the film-forming agent, the coupling agent and water are mixed uniformly at a temperature of 25° C. to obtain a premix. In order to reduce the influence of impurity ions on the performance of the surface treatment agent, the water in this embodiment can be deionized water.

[0092] S120, adjusting the pH value of the premix to a preset value using a pH adjusting agent to obtain a surface treatment agent.

[0093] In step S120, the preset value may be weak acidity, such as a pH value of 4-6. The surface treatment agent at this pH is beneficial to the reaction of the modified carbon nanomaterial with the film-forming agent and the coupling agent, and at the same time improves its reaction with the hydroxyl groups on the surface of the glass fiber to form a stronger chemical bond; on the other hand, it can also improve the stability of the surface treatment agent and reduce the occurrence of precipitation or stratification. The pH adjusting agent may be, for example, one or more combinations of citric acid, oleic acid, glacial acetic acid, etc.

[0094] In an exemplary embodiment, if Figure 5 As shown, the preparation method of the conductive agent includes:

[0095] S210, mixing the carbon nanomaterial with water to obtain a mixed solution.

[0096] In step S210, the mass ratio of the carbon nanomaterial to water may be 1:2-5, for example, the mass ratio of the carbon nanomaterial to water is 1:2, 1:3 or 1:5.

[0097] S220, adding a modifier to the mixed solution, reacting under the first preset condition to obtain an intermediate.

[0098] In step S220, the first preset condition may be 60-85°C and the time may be 0.5-2h. For example, the first preset condition may be 60°C and the time may be 2h; the first preset condition may be 80°C and the time may be 1h; the first preset condition may be 85°C and the time may be 0.5h.

[0099] S230, drying the intermediate to obtain a conductive agent.

[0100] In step S230, after obtaining the intermediate, the water therein is filtered to obtain a precipitate; and the precipitate is dried to obtain a conductive agent.

[0101] In an exemplary embodiment, if Figure 6 As shown, the present application provides a method for preparing a conductive glass fiber, comprising:

[0102] S310, immersing the glass fiber substrate in a surface treatment agent, and treating it under a second preset condition to obtain a pretreated glass fiber.

[0103] In step S310, the second preset condition includes: temperature of 20-30°C, and immersion time of 5-20s. For example, the second preset condition is: temperature of 20°C, and immersion time of 20s; the second preset condition is: temperature of 25°C, and immersion time of 10s; the second preset condition may be: temperature of 30°C, and immersion time of 5s.

[0104] S320, treating the pretreated glass fiber under a third preset condition to obtain a conductive glass fiber.

[0105] In step S320, the third preset condition includes: first treating at a temperature of 100-120°C for 5-10 minutes, and then treating at a temperature of 145-155°C for 5-10 minutes. The first treatment at a temperature of 100-120°C can avoid high-temperature decomposition of the film-forming agent, promote the reaction of the coupling agent with the hydroxyl group on the surface of the glass fiber, and the reaction of the conductive agent with the film-forming agent and the coupling agent; and the second treatment at a temperature of 145-155°C can promote further reactions between the components to form stronger chemical bonds.

[0106] Illustratively, in one embodiment, the third preset condition includes: first treating at a temperature of 110° C. for 10 min, and then treating at a temperature of 145° C. for 10 min.

[0107] In another embodiment, the third preset condition includes: first treating at a temperature of 100° C. for 8 minutes, and then treating at a temperature of 150° C. for 8 minutes.

[0108] In another embodiment, the third preset condition includes: first treating at a temperature of 120° C. for 5 minutes, and then treating at a temperature of 155° C. for 5 minutes.

[0109] In an exemplary embodiment, if Figure 7 As shown, a method for preparing a resin-based composite material is provided. The method for preparing a resin-based composite material is used to prepare the above resin-based composite material. The preparation method comprises:

[0110] S410, arranging the conductive glass fibers and the glass fibers to obtain warp yarns and weft yarns.

[0111] In step S410, the conductive glass fiber and the glass fiber may be arranged according to a preset rule, and then introduced through a creel and a tension rod to serve as warp yarns and weft yarns; wherein the preset rule may be as follows: Figure 8 The alternating arrangement shown.

[0112] S420, weaving the warp yarns and the weft yarns under a preset tension to form a reinforcing fiber layer.

[0113] In step S420, the warp yarns are woven under a preset tension to form a reinforcing fiber layer having a woven structure. The preset tension needs to be controlled within an appropriate range. Too large or too small tension will cause yarn breakage, affecting work efficiency and product qualification rate. The preset tension may be 50-150 cN, for example, the preset tension may be 50 cN, 70 cN, 100 cN, 120 cN, 150 cN. The preset tension may also be any tension value between the exemplary tension values, for example, the preset tension may also be any tension value between 70-120 cN.

[0114] S430, impregnating the reinforcing fiber layer with a resin matrix to obtain a resin-based composite material.

[0115] In step S430, a vacuum infusion method may be used to make the resin matrix infiltrate the reinforcing fiber layer, and after curing, a resin-based composite material may be obtained, wherein the curing process may be a gradient composite process of 50° C. for 4 hours and 80° C. for 8 hours.

[0116] In order to more clearly explain the technical solution of the present application, the present application lists specific embodiments of the resin-based composite material, and the beneficial effects of selecting the above-mentioned range of the content of each component will be explained by giving specific experimental data through specific embodiments.

[0117] Preparation Example

[0118] It should be noted that, unless otherwise specified, the raw materials in the following preparation examples can be obtained from commercial sources. The carbon nanomaterial can be a carbon nanotube and graphene in a mass ratio of 1:1.

[0119] Preparation Example 1: A method for preparing a conductive agent, comprising the following steps:

[0120] The carbon nanomaterial is mixed with water to obtain a mixed solution; a modifier is added to the mixed solution, and the mixture is reacted at a temperature of 80°C for 1.5 hours to obtain an intermediate; the intermediate is cooled and filtered to obtain a precipitate, and the precipitate is dried to obtain a conductive agent. The modifier is dodecyl dimethyl benzyl ammonium chloride; and the weight ratio of the carbon nanomaterial, the modifier and water is 1:0.5:3.

[0121] After mixing the unmodified carbon nanomaterial and the modified carbon nanomaterial (i.e., the conductive agent) with water, the stability of the mixture was observed after standing for 0 h and 24 h. Figure 9a and Figure 9b It can be seen that after the carbon nanomaterials are modified in this preparation example, the obtained conductive agent can be stably dispersed in water and can remain unstratified for 24 hours, indicating that the conductive agent in this preparation example can maintain good dispersion stability in the surface treatment agent of the aqueous system.

[0122] In order to more clearly explain the technical solution of the present application, the present application also lists Preparation Examples 2-5 of the conductive agent, wherein the formula of Preparation 2-5 is shown in Table 1. It should be noted that, except for the parameters listed in Table 1, the other parameters of Preparation Example 2-5 are basically the same as those of Preparation Example 1.

[0123] Wherein, the ratio C1 is the mass ratio of dodecyldimethylbenzylammonium chloride to octadecyl-(2-sulfite)-ethyldimethylammonium.

[0124] The ratio C2 is the mass ratio of the carbon nanomaterial to the modifier.

[0125] The conductive agent prepared by the method of each preparation example was mixed with water and allowed to stand for 0 h, 24 h, 48 h, 72 h, and 96 h, and the system was observed to see whether precipitation, stratification, etc. occurred. The observation results were recorded in Table 1.

[0126] Table 1 Conductive agent formula and stability test table

[0127]

[0128] Note: “√” in Table 1 indicates that this modifier is used, and “ / ” indicates that this modifier is not used.

[0129] It can be seen from the data in Table 1 that the carbon nanomaterial treated with the modifier in the preparation example can significantly improve its dispersibility in water, and as the amount of the modifier increases, the retention time of the dispersion stability of the carbon nanomaterial in water is prolonged. Among them, when the mass ratio of the carbon nanomaterial to the modifier is 1:1.0-2.0, the modified carbon nanomaterial can maintain a long-term dispersion stability in water.

[0130] Example

[0131] It should be noted that, unless otherwise specified, the raw materials in the following examples can be obtained from the market. Among them, the film-forming agent in the following examples can be bisphenol A epoxy resin emulsion; the silane coupling agent can be 3-glycidyloxypropyl triethoxysilane; the penetrant can be JFC fatty alcohol polyoxyethylene ether; the lubricant can be polyethylene glycol; and the pH regulator can be oleic acid.

[0132] Embodiment 1: A method for preparing a surface treatment agent comprises the following steps:

[0133] (1) 1.0 wt% of a conductive agent, 15 wt% of a film-forming agent, 5 wt% of a coupling agent, 0.5 wt% of a penetrant, 0.5 wt% of a lubricant and 78.0 wt% of water were mixed and stirred at 25° C. to obtain a premix; wherein the conductive agent was prepared according to Preparation Example 1.

[0134] (2) The pH value of the premix is ​​adjusted to 6 using a pH adjuster to obtain a surface treatment agent.

[0135] In order to more clearly explain the technical solution of the present application, the present application also lists Examples 2-14 of the preparation method of the surface treatment agent, wherein the formulas of Examples 2-14 are shown in Table 2.

[0136] Table 2 shows a specific example of the preparation method of the surface treatment agent in the present application. It should be noted that, except for the parameters listed in Table 2, other parameters of Examples 2-14 and Example 1 are substantially the same.

[0137] Among them, the ratio C3 is the mass ratio of the conductive agent, the coupling agent, and the film-forming agent.

[0138] Table 2 Formulation of surface treatment agent raw materials (unit: wt%)

[0139]

[0140] Table 2 (Continued) Formulation of raw materials of surface treatment agent (Unit: wt%)

[0141]

[0142] Performance Testing

[0143] According to the following method, the surface treatment agent in the above embodiment is used to prepare conductive glass fiber, and the resistivity and wear resistance of the conductive glass fiber and untreated glass fiber (recorded as comparative example 1) and glass fiber with unmodified carbon nanomaterial conductive agent added (recorded as comparative example 2) are tested, and the test results are recorded in Table 3.

[0144] The method for preparing the conductive glass fiber comprises:

[0145] The glass fiber substrate was immersed in the surface treatment agent at a temperature of 25° C. for 10 seconds to obtain a pretreated glass fiber. The pretreated glass fiber was first kept at a temperature of 120° C. for 10 minutes and then kept at a temperature of 150° C. for 10 minutes to obtain a conductive glass fiber.

[0146] 1. Resistivity: According to the method in GB / T 32993-2016 "Determination of volume resistivity of carbon fiber", the resistivity of the conductive fiber is tested. The smaller the resistivity, the better the conductive performance of the conductive fiber.

[0147] 2. Wear resistance: Take a certain length of conductive glass fiber, tie a 5g weight to one end of the conductive glass fiber and fix it on the FFZ622 yarn wear resistance tester. After wrapping cotton cloth on the friction roller of the tester, rub the conductive glass fiber repeatedly for 50 times, record the mass after friction, and calculate its weight loss rate. The lower the weight loss rate, the better the wear resistance, and the stronger the bonding force between the surface treatment layer and the glass fiber matrix.

[0148] Table 3 Performance test table of conductive glass fiber

[0149]

[0150] Table 3 (Continued) Performance test table of conductive glass fiber

[0151]

[0152] Combining the data in Table 2 and Table 3, it can be seen that the resistivity of the glass fiber treated with the surface treatment agent of the present application is significantly reduced, indicating that it has good conductivity. After rubbing the conductive glass fiber 50 times, its weight loss rate is within 10%, indicating that it has good wear resistance and good bonding between the surface treatment layer and the glass fiber matrix.

[0153] Application Examples

[0154] Application Example 1: A method for preparing a resin-based composite material, comprising the following steps:

[0155] (1) Immerse the glass fiber substrate in a surface treatment agent at a temperature of 25° C. for 10 seconds to obtain a pretreated glass fiber. Maintain the pretreated glass fiber at a temperature of 120° C. for 10 minutes and then at a temperature of 150° C. for 10 minutes to obtain a conductive glass fiber. The conductive glass fiber is prepared according to Example 1.

[0156] (2) Conductive glass fiber and glass fiber are woven at a mass ratio of 1.0:1 and a tension of 100 cN to obtain a reinforced fiber fabric to be used as a reinforcing fiber layer of a resin-based composite material.

[0157] (3) 32.3 kg of resin matrix was impregnated into 67.7 kg of reinforcing fiber fabric, and after curing, a resin-based composite material was obtained.

[0158] In order to more clearly explain the technical solution of the present application, the present application also lists application examples 2-18 of the preparation method of the resin-based composite material, wherein the setting parameters of application examples 2-18 are shown in Table 4. It should be noted that, except for the parameters listed in Table 4, the other parameters of application examples 2-18 are basically the same as those of application example 1.

[0159] Wherein, the ratio C4 is the mass ratio of the conductive glass fiber to the glass fiber.

[0160] Table 4 Parameter setting table of application example

[0161]

[0162] Table 4 (Continued) Parameter setting table for application example

[0163]

[0164] Control Example: The main difference between this control example and the application example is that the conductive glass fiber is replaced by an equal amount of untreated glass fiber.

[0165] Performance Testing

[0166] The performance of the corresponding use cases 1-18 is tested according to the following method, and the test results are recorded in Table 5.

[0167] 1. Mechanical properties: The interlaminar shear strength, in-plane shear strength and tensile strength of the conductive glass fiber fabric reinforced epoxy resin composite material were tested according to ISO14130, ASTM D7078 and ISO527-5 respectively.

[0168] 2. Complete wetting time: Place the 600mm×430mm fabric horizontally, pour the epoxy resin along the 0° direction, and use a stopwatch to record the time of complete wetting.

[0169] 3. Lightning protection performance: Lightning test is carried out in accordance with IEC 61400-24:2019, and ultrasonic non-destructive flaw detector is used to observe the internal damage after lightning strike. Among them, no damage to the interface layer is recorded as A, and local damage to the interface layer is recorded as B.

[0170] Table 5 Performance test table of application examples

[0171]

[0172] Table 5 (Continued) Performance test table of application examples

[0173]

[0174] Combining the data in Table 2 and Table 5, it can be seen that the present application uses conductive glass fiber and glass fiber as the reinforcing fiber layer, which can improve the mechanical properties of the composite material while giving it excellent lightning protection performance. In addition, by controlling the mass ratio of conductive glass fiber and glass fiber, the composite material can have good processing performance.

[0175] It can also be seen from Tables 2 to 5 that Examples 2-3, Examples 6-7 and Example 10 have better comprehensive performance. Therefore, by adjusting the mass percentage of each component of the surface treatment agent, when the conductive agent is 2-4wt%; the film-forming agent is 18-22wt%; the coupling agent is 8-12wt%; the penetrant is 1.0-1.8wt%; the lubricant is 1.0-1.5wt%, the mass ratio of the carbon nanomaterial and the modifier in the conductive agent is 1:0.8-1.5, and the mass ratio of the conductive agent, the silane coupling agent, and the film-forming agent is 1:3-5:5-9.5, the components of the surface treatment agent can maintain good dispersion stability, and the conductive glass fiber prepared by the surface treatment agent and the composite material prepared by the conductive glass fiber can have better mechanical properties.

[0176] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0177] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A resin-based composite material, characterized in that: The resin-based composite material comprises a resin matrix and a reinforcing fiber layer, wherein the resin matrix is ​​filled into the reinforcing fiber layer; The reinforcing fiber layer includes conductive glass fiber and glass fiber in a mass ratio of 0.5-2.0:

1.

2. The resin-based composite material according to claim 1, characterized in that: The percentage of the mass of each component of the resin-based composite material to the total mass of the resin-based composite material is as follows: Resin matrix 30-50wt%; Reinforced fiber layer 50-70wt%.

3. The resin-based composite material according to any one of claims 1 or 2, characterized in that: The conductive glass fiber comprises a glass fiber matrix and a surface treatment layer arranged on the surface of the glass fiber matrix.

4. The resin-based composite material according to claim 3, characterized in that: The surface treatment layer includes a surface treatment agent, and the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows: Wherein, the conductive agent includes modified carbon nanomaterials.

5. The resin-based composite material according to claim 4, characterized in that: The modified carbon nanomaterial comprises a carbon nanomaterial and a modifier, wherein the modifier comprises an amine modifier, and the carbon chain length of the amine modifier is greater than or equal to C10.

6. The resin-based composite material according to claim 5, characterized in that: The mass ratio of the carbon nanomaterial to the modifier is 1:0.5-2.

0.

7. The resin-based composite material according to claim 5, characterized in that: The modifier includes a combination of one or more of dodecyldimethylbenzylammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium; The film-forming agent includes one of water-based epoxy resin emulsion and water-based polyurethane emulsion or a combination of the two; The coupling agent includes one of epoxy silane coupling agents and amino silane coupling agents or a combination of the two.

8. The resin-based composite material according to claim 4, characterized in that: The surface treatment agent also includes: A penetrant, the mass of which accounts for 0.5-2wt% of the total mass of the surface treatment agent; and / or, a lubricant, wherein the mass of the lubricant accounts for 0.5-2wt% of the total mass of the surface treatment agent.

9. A method for preparing a resin-based composite material, characterized in that: The method for preparing the resin-based composite material is used to prepare the resin-based composite material according to any one of claims 1 to 8, and the method comprises: Arranging the conductive glass fiber and the glass fiber to obtain warp yarn and weft yarn; Weaving the warp yarns and the weft yarns under a preset tension to form the reinforcing fiber layer; The resin matrix is ​​impregnated into the reinforcing fiber layer to obtain the resin-based composite material.

10. The method for preparing a resin-based composite material according to claim 9, characterized in that: The preset tension is 50-150 cN.